Properties of Internet and telephone data collection methods in a stated choice value of time study context - Maria Börjesson; Staffan Algers (Journal of Choice Modelling, 2011)
We analyse Internet and telephone Stated Choice (SC) survey methods in the context of the Swedish value of time study 2008. In this study, extensive piloting and follow-up surveys were undertaken to assure high quality data. We use these data and data from the main survey to analyse properties of the different data collection methods. One conclusion is that the Internet gives less random error in the SC data. On the other hand, the response rate drops when the Internet is the only response and recruiting mode. A mixed mode survey, where the Internet is the primary method but where respondents are knowingly subject to a telephone follow up survey, is found to give substantially higher Internet response rates. If the telephone follow-up does not include SC questions, the value of time result will still be biased. However, a large part of this bias seems to be explained by socio-economic data, such as income and age, which are cheaper to collect.
Keywords: 330; stated choice; data collection; value of time; mixed mode surveys; response error